Effect of Molecular Chain Structure on Fracture Mechanical Properties of Aeronautical Polymethyl Methacrylate Using Extended Digital Image Correlation Method - Wei Shang; Xiaojing Yang; Xinhua Ji; Zhongxian Liu (Advances in Materials Science and Engineering)
The main purpose of this work is to investigate the fracture mechanical properties of aeronautical polymethyl methacrylate, which has been treated with directional tensile technology. Because of the special processing of directional polymethyl methacrylate, the molecular chain structures are different in different directions. The mechanical properties depend on the specific molecular chain structures. We use extended digital image correlation to measure the displacement field near the tip of the crack when the cracks grow in different directions in directional polymethyl methacrylate. We then tested the critical load for different specimens and analyzed the fracture morphology of the different specimens. Thanks to the experimental results, a molecular chain model of directional polymethyl methacrylate could be established. The analysis results using the molecular chain model are consistent with the experiments, which confirms the reliability of the molecular chain model.